Prevalence and infection intensity of the ovarian parasite Marteilioides chungmuensis during an annual reproductive cycle of the oyster Crassostrea gigas - Ngo, Thao; Berthe, Franck; Choi, Kwang-sik (Inter-Research, 2003)
The occurrence of Marteilioides chungmuensis, a protozoan paramyxean parasite in the reproductive system of the Pacific oyster Crassostrea gigas, was observed at Gosung Bay, Korea. Seasonal variation in gonad development was investigated in a suspended cultured oyster population. Gametogenesis began in February and first-spawning was observed between mid and late June when surface water temperature reached 22 to 25degreesC. Spawning activity extended from mid June to late September, with 2 marked spawning peaks in June and August. Histological examination indicated that gonad development paralleled seasonal fluctuations in water temperature. Spawning in late June was partly associated with a sudden drop in salinity due to large freshwater inputs to the Bay with the summer monsoon. M chungmuensis occurred in developing and fully mature eggs of spawning oysters in late June to January, but were not observed from February to May. Monthly mean infection intensity was high in late June when most oysters had their first spawning period. The infection level was also relatively high in late August and November, when oysters were spawning or had completed spawning. Several oysters collected in November (11.4 %) and December (16.3 %) carried a large quantity of ripe but M chungmuensis-infected eggs, suggesting that infection also causes spawning failure by delaying spawning and destroying ripe oocytes.